2011
DOI: 10.1002/jor.21432
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E blended Uhmwpe may have the potential to reduce bacterial adhesive ability

Abstract: Biomaterial-associated infection (BAI), a clinical problem resulting in septic failure of joint replacement implants, is initiated by bacterial adhesion, often by Staphylococcus epidermidis. Ultra high molecular weight polyethylene (UHMWPE) is a material of choice for joint replacement; reducing the adhesion of S. epidermidis to the polymer could be a means to decrease infection. We examined the adhesion of two ATCC and one clinical strain of S. epidermidis to standard polyethylene (PE), vitamin E blended UHMW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 40 publications
(51 reference statements)
4
46
0
1
Order By: Relevance
“…An important limitation of that study was that 90 minutes of bacterial exposure may not have provided an accurate measure for biofilm formation on the surface of a material since bacteria require roughly 24 hours to form a mature biofilm [23]. In a study by Banche et al [1], three material types were exposed to an initial inoculum of 10 7 CFUs/mL for various times including 24 hours and 48 hours. These tests were not performed under flow but rather under static conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An important limitation of that study was that 90 minutes of bacterial exposure may not have provided an accurate measure for biofilm formation on the surface of a material since bacteria require roughly 24 hours to form a mature biofilm [23]. In a study by Banche et al [1], three material types were exposed to an initial inoculum of 10 7 CFUs/mL for various times including 24 hours and 48 hours. These tests were not performed under flow but rather under static conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that implant materials alone, such as black silicon and silicon nitride, may have the ability to prevent bacterial attachment or eradicate bacteria that come in contact with the material [7,10]. Additionally, previous reports have suggested that the addition of vitamin E to UHMWPE may prevent the adhesion of bacteria to its surface and thus reduce the risk of biofilm formation and subsequent infection [1,5,12]. It has been proposed that bacteria may have increased affinity to adhere to oxidized UHMWPE surfaces and form biofilms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomaterial associate infections (BAI) are still an issue in total joint replacement (TJR) surgery, [1][2][3][4] where often result in a series of implant-related sequelae that can lead to implant removal with clinical and economic consequences of significant importance. 5 The initial bacterial adhesion and subsequent growth of microorganisms to the biomaterials implant surface are complex processes related to physico-chemical interactions between substratum and microorganisms.…”
Section: Introductionmentioning
confidence: 99%